2022
DOI: 10.3390/vaccines10071037
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and Lymphocyte Profiles in Dogs with Atopic Dermatitis after Allergen-Specific Immunotherapy

Abstract: Canine atopic dermatitis (cAD) is a chronic and recurrent inflammatory and pruritic skin disease in dogs. Currently, allergen-specific immunotherapy (ASIT) is the only identified disease-modifying intervention for allergic diseases. It decreases the symptoms triggered by allergens and prevents recurrence of the disease in the long-term. The aim of our research was to determine how immunotherapy changes the proportion of lymphocyte subsets in dog peripheral blood and the levels of cytokines secreted by these ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 42 publications
2
19
1
Order By: Relevance
“…[8][9][10] In dogs, similar findings have been shown including an increase of Treg cells in peripheral blood 11,12 and interleukin (IL)-10 serum concentrations, 11 change in allergen-specific serum IgE and IgG concentrations, 13 and reduction of inflammatory plasma cytokine concentrations. 12 Allergen-specific immunotherapy (ASIT) typically consists of an induction and a maintenance phase. During the induction phase, the amount of injected allergens is increased gradually until immunological tolerance is reached.…”
Section: O R I G I N a L A R T I C L E Efficacy Of Short-term Combina...mentioning
confidence: 55%
See 1 more Smart Citation
“…[8][9][10] In dogs, similar findings have been shown including an increase of Treg cells in peripheral blood 11,12 and interleukin (IL)-10 serum concentrations, 11 change in allergen-specific serum IgE and IgG concentrations, 13 and reduction of inflammatory plasma cytokine concentrations. 12 Allergen-specific immunotherapy (ASIT) typically consists of an induction and a maintenance phase. During the induction phase, the amount of injected allergens is increased gradually until immunological tolerance is reached.…”
Section: O R I G I N a L A R T I C L E Efficacy Of Short-term Combina...mentioning
confidence: 55%
“…In humans, the mechanism behind ASIT includes the induction of allergen-specific regulatory T (Treg) cells and their cytokines, induction of allergenspecific immunoglobulin (Ig)G4 concentrations and reduction of both the ratio of Th2/Th1 cytokines and serum allergen-specific IgE. [8][9][10] In dogs, similar findings have been shown including an increase of Treg cells in peripheral blood 11,12 and interleukin (IL)-10 serum concentrations, 11 change in allergen-specific serum IgE and IgG concentrations, 13 and reduction of inflammatory plasma cytokine concentrations. 12 Allergen-specific immunotherapy (ASIT) typically consists of an induction and a maintenance phase.…”
Section: O R I G I N a L A R T I C L E Efficacy Of Short-term Combina...mentioning
confidence: 83%
“…However our previous studies found that the drug may have a more complex mechanism of action (Jasiecka-Mikołajczyk et al 2021). Considering the fact that T and B cells are involved in the pathophysiology of AD in dogs (Olivry et al 1999, Nuttall et al 2002, Schlotter et al 2011, Majewska et al 2022, the depletive effect of the drug toward these cells may contribute to the beneficial effects of OCL in the treatment of skin allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory reaction in this disease is caused by an imbalance between Th2 and Th1 cells, resulting in activation of B cells, which are stimulated to produce IgE. Binding of allergen-specific IgE to mast cells causes degranulation of these cells and the secreted inflammatory mediators lead to inflammation (Majewska et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, AD is a chronically relapsing inflammatory skin disease, and as such, an influx of activated white blood cells, especially T cells, is a hallmark of AD. For this reason, T cells and their derived cytokines and chemokines have been extensively modeled to gain insight into the local and systemic immune milieu of the disease (Bruet et al., 2015; Majewska et al., 2022; Rostaher et al., 2018, and Bauman et al., 2022).…”
Section: In Vitro Inflammatory Skin Disease Modelsmentioning
confidence: 99%